A generalizable and turnable engineered ecosystem provides a clear route to prosperity and well-being to harness the world’s aquatic “blue” food systems to help end hunger: A perspective - Li, Shengwen Calvin; He, Jian-guo (Frontiers in Food Science and Technology, 2022)
Seafood security is essential in modern society. In 2013, Bush and colleagues stated, “Aquaculture, farming aquatic organisms, provides nearly 50% of the world's seafood supply, with a value of U.S. $125 billion. It makes up 13% of the world's animal-source protein (excluding eggs and dairy) and employs an estimated 24 million people(Bush et al., 2013). With the increased human population and reduced fishing resources(Bidgood, 2013), humans increasingly rely on aquacultural products for many countries' primary protein sources (Godfray et al., 2010). Aquacultural productivity has been improving in recent years, and in certain countries, the aquaculture output is more than the fishing output. For example, Chinese aquaculture production is more than fishing output, which provides one-third of animal protein. Thus, intensive aquaculture has become the main supply of global aquatic products (FAO)(Koohafkan and Furtado, 2004). In recent years the part of the country's for each person consumption of aquaculture products has been 130 kg in some countries (Ice Lands)(Naylor et al., 2000). Here, we illustrated the road blocker in farmed shrimp production and provided our resolution. The global white spot syndrome (WSS) pandemic, caused by the white spot syndrome virus (WSSV), bears a devastating economic loss in farmed shrimp production, jeopardizing seafood security. Currently, there is no effective control for WSS. Conventional single-species intensive farming eliminates the spatiotemporal interaction between different species. We hypothesize that establishing the spatiotemporal interface of a predator-prey may control the WSS outbreak. We search for the pathways for the mechanisms by which predator-prey species interact and compete across spatial scales to characterize WSSV dispersal at regional scales for the local spatiotemporal structure of viral transmission. Thus, we create a generalizable and tunable engineered ecosystem that provides a clear route to prosperity and well-being to harness the world’s aquatic ‘blue’ food systems to help end hunger.